The role of serum ferritin as a biomarker of iron and inflammation in anemia: a systematic literature review - Kedaton, Rafi Andyah Arum; Devi, Nabila Sinta; Kusworini, Kusworini; Wardani, Diadjeng Setya (Poltekkes Kemenkes Bandung, 2026)
Background: Anemia remains a major global health concern, particularly in low- and middle-income countries where distinguishing Iron Deficiency Anemia (IDA) from Anemia of Inflamation (AI) remains diagnostically challenging. Hemoglobin alone cannot differentiate these conditions, necessitating more specific biomarkers. Serum ferritin, the primary iron-storage protein, reflects body iron reserves but is also elevated during inflammation through interleukin-6-mediated hepcidin induction. Objective: This review examines the dual role of ferritin as an iron biomarker and an inflammatory marker. Methods: A literature search was conducted in PubMed, ScienceDirect, SpringerLink, and the Cochrane Library with a ten-year publication limit. Of the 89 articles identified, only eight studies met the inclusion criteria and directly evaluated the relationship between ferritin, iron status, and inflammatory processes. Results: Ferritin remains a key indicator of iron reserves, but its interpretation needs to take into account the inflammatory status. Conclusion: The combination of ferritin with inflammatory biomarkers such as C-Reactive Protein (CRP)and Alpha-1-acid glycoprotein (AGP) improves the diagnostic accuracy for anemia related to both iron deficiency and inflammation.